Strategi Pembinaan Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di Sekolah Menengah Kejuruan Negeri di Bangka Selatan - Aloi Kamarasyid (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2019)
The function and the aim of education is to create the quality human resource. The education must be done professionally by the teachers whose pedagogic competence, personality competence, professional competence, and social competence of education. Which is an instrument to perform the change at all aspecs. To form the education which has a high quality is needed the good cooperation of government, society, teachers and staff so that its aim care be teached according to the vision and mission. School is an institution which is managed by a leader whose part to perform a process of education in the school. Head master is a supervisor of the development of the leader of the teachers and the other personal in the school. In reaching the aim of education. He or she must give a support, guidance and a chance for growing the skill and ability of the teachers such as a guidance and execution of educational reformation and teaching, choosing of instrument of lesson and methods of teaching well and discipline, method of systimatic evaluation regarding the phase of all process of teaching. In performing the building, head master should observe the main principles, namely: (1) Science; by following the principles: systematic, regular, programmed, continue; objective, according to data and information by using instrument which can give the accurate data and information; able to be analysed and able to measure or value on performing of teaching. (2) Democracy. (3) Cooperative. (4) Constructive and creative. Some efforts to develop the professional teacher included three programs: (1) Program of pre-service, (2) program of in-service education, (3) program of-in service training. Fungsi dan tujuan pendidikan adalah untuk menciptakan sumber daya manusia yang berkualitas. Pendidikan itu harus dilakukan secara profesional oleh guru-guru yang mempunyai kompetensi pedagogik, kompetensi kepribadian, kompetensi profesional, dan kompetensi sosial. Pendidikan adalah alat untuk mengadakan perubahan di semua bidang. Untuk mewujudkan pendidikan yang memiliki kualitas tinggi dibutuhkan kerja sama baik dari pemerintah, masyarakat, para guru dan stafnya, sehingga tercapai tujuannya sesuai dengan visi-misinya. Sekolah merupakan lembaga dikelola oleh seorang pemimpin yang berperan menyelenggarakan proses pendidikan di sekolah. Kepala sekolah merupakan supervisi yang tertuju kepada perkembangan kepemimpinan guru-guru dan personel sekolah lainnya dalam mencapai tujuan pendidikan. Ia harus memberikan dorongan, bimbingan, dan kesempatan bagi pertumbuhan keahlian dan kecakapan guru-guru, seperti bimbingan dan pelaksanaan pembaharuan pendidikan dan pengajaran, pemilihan alat-alat pelajaran dan metode-metode mengajar yang lebih baik, cara-cara penilaian yang sistematis terhadap fase seluruh proses pengajaran. Dalam melaksanakan pembinaan kepala sekolah hendaknya memperhatikan prinsip-prinsip utama, yaitu: (1) Ilmiah. Dengan menganut asas: Sistematis, teratur, terprogram, dan kontinue; Objektif, berdasarkan pada data dan informasi; Menggunakan instrumen (alat), yang dapat memberikan data/ informasi yang akurat, dapat dianalisis, dan dapat mengukur ataupun menilai terhadap pelaksanaan pembelajaran. (2) Demokrasi. (3) Kooperatif. (4) Konstruktif dan kreatif. Beberapa usaha pengembangan profesionalisme guru meliputi tiga program yaitu: (1) Program pre-service education. (2) Program in-service education. (3) Program in-service training.